Local Government and Justice in Strategic Asset Transactions: A Case Study of Indonesia’s National Strategic Project in Bulungan Regency - Syaprillah, Aditia; Ansar, Ferdy; Shahnaz, Liza; Rohman, Arif; Sukumaran, Shantini (Universitas Lampung, 2026)
The implementation of Indonesia’s National Strategic Projects (PSN) increasingly relied on the exchange of local government assets, particularly land, through ruilslag mechanisms, raising critical issues of justice, accountability, and the protection of public interests. Local governments occupied an ambiguous position as both public authorities and civil law actors, complicating the governance of public asset transfers. Using a normative-empirical legal research method, this study analyzed statutory regulations, regional legal instruments, and official asset swap documents, supported by a case study of Bulungan Regency and interviews with key stakeholders. The findings revealed procedural inconsistencies, limited transparency, and unequal bargaining power in asset transactions, indicating that existing legal frameworks were often inadequately implemented to ensure substantive justice. The study concluded that local governments require stronger institutional, fiscal, and regulatory support to manage public assets effectively, and that PSN-related asset exchanges must integrate legal safeguards, public participation, and long-term social considerations to avoid becoming merely technocratic instruments of central government policy.